(3eTcdGJ GdeSFhdjI GdeOfjI GdfGLeI Yf GLQGA YedjGJ GdGSJfSGN Ydi GdHTQ (B: s (3OQGSI ebGQfI (B/ s - (3fSQjf SdjeGf MSf efUhQs; (3eMeO TcQi SQhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3cGf GdebUhO ef gPI GdOQGSI JHjGf GdCMcGe GdbGfhfjI heTcdGJ GdeSFhdjI GdeOfjI GdJi jecf Cf JfLe LQGA JWHjb gPG GdfhY ef GdJbfjGJ GdYdejI GdMOjKI Ydi GdHTQ SjeG eY JYOO CTcGd gPI GdJbfjI hGNJdGa GdgOa GdefThO dcd efgG(B.(3hgPI GdOQGSI gi YHGQI Yf fXQI eSJbHdjI deG gh efJXQ MOhKI ShGA ai GdRef GdbQjH Ch GdHYjO HjO CfgG JbfjI bGOeI dGeMGdI hgi OQGSI GaJQGVjI ai eYXegG jSHb GdhbJ hJYGdL eTcdGJ GdeSFhdjI GdeOfjI GdJi ef GdeJhbY Ef jKjQgG JWHjb gPI GdJbfjGJ GdYdejI Ydi GdHTQs
(3GWQhMI(B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2008s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B502-518s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GSJfSGN GdHTQs; (3GdGSJfSGNs; (3GdeSFhdjI GdeOfjIs; (3GdGYUGA GdHTQjIs; (3GdGSJJFGe s; (3GdCLfgs; (3GdbGfhf GdeUQjs; (3GdbGfhf GdGfLdh GeQjcjs; (3GdbGfhf GdHQjWGfjs; (3GdbGfhf GdGeQjcjs; (3GdbGfhf GdaQfSjs; (3GdfWa GdHTQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs